From MASTER-Web to AGATHE: the evolution of an architecture for manipulating information over the Web using ontologies - DOI: 10.3395/reciis.v2i1.137en - Fred Freitas; Luciano Cabral; Rinaldo Lima; Eunice Palmeira; Guilherme Bittencourt; Bernard Espinasse; Sébastien Fournier (Instituto de Comunicação e Informação Científica e Tecnológica em Saúde (Icict) da Fundação Oswaldo Cruz (Fiocruz), 2008)
This article presents two architectures for information gathering systems on restricted Web domains, for example the academic or the biologic domain. This text processing is based on the use of domain-related ontologies employing them as a well-defined and understandable semantic model for the software. If, on one hand, the solution here presented cannot be scaled to the entire Web, on the other hand, the offered services are more versatile and precise and able to combine information with well-defined relationships distributed over the Web. The presented systems are still able to draw inferences about the information present in the Web about these domains. As a proof of concept, we present experiments with good results in two distinct domains, showing the feasibility and portability between domains of the presented solution besides presenting a high degree of reuse during the portability.